Impact of Foreign Direct Investment on Economic Growth of India - Keerti G Kulkarni,; Dr H N Shivaprasad,; Dr M M Munshi, (International Journal of Scientific Research and Management (IJSRM), 2021)
International capital flows have a significant role for growth and development of recipient countries by providing necessary capital, resources and technology. One aspect of such international investment is Foreign Direct Investment (FDI) which has become an important source of external finance since they are considered as more stable and prominent source of capital inflows. The present study has been conducted to evaluate long-run and short-run impact of FDI on economic growth of India. Gross Domestic Product (GDP) has been considered as indicator of economic growth for this study. The empirical analysis has been conducted using Autoregressive Distributed Lag Approach (ARDL) of Cointegration. The period of study was 1991-92 to 2018-19. The findings of the study indicate presence of long-run relationship between FDI and economic growth of India. The study concludes that Foreign Direct Investment helps to enhance economic growth of India.